Allosteric Regulation of Transport Activity by Heterotrimerization of Arabidopsis Ammonium Transporter Complexes in Vivo([C])([W])([OA]) - Yuan, Lixing (American Society of Plant Biologists, 2013)
Ammonium acquisition by plant roots is mediated by AMMONIUM TRANSPORTERs (AMTs), ubiquitous membrane proteins with essential roles in nitrogen nutrition in all organisms. In microbial and plant cells, ammonium transport activity is controlled by ammonium-triggered feedback inhibition to prevent cellular ammonium toxicity. Data from heterologous expression in yeast indicate that oligomerization of plant AMTs is critical for allosteric regulation of transport activity, in which the conserved cytosolic C terminus functions as a trans-activator. Employing the coexpressed transporters AMT1;1 and AMT1;3 from Arabidopsis thaliana as a model, we show here that these two isoforms form functional homo- and heterotrimers in yeast and plant roots and that AMT1;3 carrying a phosphomimic residue in its C terminus regulates both homo- and heterotrimers in a dominant-negative fashion in vivo. (15)NH(4)(+) influx studies further indicate that allosteric inhibition represses ammonium transport activity in roots of transgenic Arabidopsis expressing a phosphomimic mutant together with functional AMT1;3 or AMT1;1. Our study demonstrates in planta a regulatory role in transport activity of heterooligomerization of transporter isoforms, which may enhance their versatility for signal exchange in response to environmental triggers.